Intestinal microbiome as effective regulator of enteral and central nervous system activity - V. T. Ivashkin; K. V. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2018)
Aim of review. To study and generalize in the single review the data on prebiotics and probiotics effect on microbiome, intestinal motility and enteric nervous system. Key points. Objective data indicate the ability of enteric bacteria to regulate electrophysiologic thresholds of enteric neurons and to produce a spectrum of neurotransmitters. These data presumes the presence of direct microbiota-induced responses of enteric nervous system as well as its development and intestinal glial cells hemostasis maintenance. No evidence of direct involvement of these neurotransmitters in regulation of proximal enteral neurons synaptic activity is obtained. However the fact of neurotransmitter production in close proximity to intestinal wall creates a basis for the further studies. Conclusion. Studying of probiotics and probiotics effect on enteric nervous system is of enormous interest. Accumulated data change the current concept on human microbiome and its potential, however further clinical trials required.